Giant recurrent infantile myofibromatosis of the leg in a 3 year-old - Youssef Mohammed (Wolters Kluwer Medknow Publications, 2009)
Infantile myofibromatosis is a rare mesenchymal disorder of infancy and childhood characterised by the formation of tumours in the soft tissues, muscles, bones and viscera. Only 61 cases have been reported in the literature. This paper describes the management of a 3 year-old boy with extensive IMF of the right leg.